Analisis Kinerja Keuangan Pada Perusahaan Transportasi Yang Terdaftar Di Bursa Efek Indonesia: Studi Kasus Pada PT. Blue Bird Tbk Dan PT. Buana Lintas Lautan Tbk - Dewi Ummi Safitri; Masdar Mas’ud; Nur Alam (CV ODIS, 2022)
This research aims to analyze the financial performance of transportation companies PT. Blue Bird and PT. Buana Listy Tama based on liquidity ratio analysis method, profitability ratio and solvency ratio, period 2014-2018. This research period was conducted for 5 years, namely in 2014-2018. The types of data used in this study are quantitative and qualitative data. The data source used is secondary data in the form of the annual financial statements of transportation companies from 2014-2018 obtained from the Stock Exchange Investment Gallery of the Faculty of Economics, Muslim University of Indonesia. The research population is a sub-sector transportation company on the Indonesia Stock Exchange (IDX) in the period 2015-2019, namely 32 sub-sector transportation companies listed on the Indonesia Stock Exchange (IDX). The sample selected based on purposive sampling techniques was obtained by 2 companies. Descriptive analysis techniques used to analyze data use three ratios. Based on the results of analysis of financial performance data on the company PT. Blue Bird Tbk has not been going well, because based on the results of calculations made with liquidity, solvency, and profitability ratios, many have decreased due to the company's financial management has not been good. While the financial performance of the company PT. Buana Listy Tama Tbk did not go so well, because based on the results of calculations made with liquidity, solvency, and profitability ratios, many experienced a decrease especially in their perishability ratio due to the company's financial management can be said to be bad.